A Correlation Between Knowledge And Motivation With The Visits Of Mothers With Toddlers To The Posyandu In The Working Area Of Lingkar Timur Health Center In 2024 - Agustami, Hesti Tri; Saputri, Meita Tria; Nurjanah, Nimas Ayu Lestari (Universitas Dehasen Bengkulu, 2025)
Posyandu is a community-based health facility that provides services for 5 main activities of Maternal and Child Health (KIA), Family Planning (KB), Nutrition, Immunization and Prevention and Control of Diarrhea which are carried out from, by, for and with the community. In 2022, the number of visits by mothers and toddlers at the posyandu in the Lingkar Timur Health Center work area was 85%, while in 2023 the coverage of visits by mothers and toddlers decreased to 68%). The low coverage of maternal participation in the posyandu can be seen from the toddler weighing data. Several factors that cause the low coverage of maternal participation in the posyandu include: maternal knowledge, posyandu activities, toddler nutritional status, motivation, maternal attitude and distance to the posyandu. The purpose of this research was to determine the relationship between knowledge and motivation and visits by mothers and toddlers to the posyandu. This research is an observational analytical study with a cross-sectional approach. This research was conducted in the Lingkar Timur Health Center Work Area on June 1-24, 2024. The number of samples in this study was 50 toddlers in the Lingkar Timur Health Center Work Area. The sampling technique used the total sampling method and the analysis used the chi-square statistical test. The results of the research showed that there was a corelation between knowledge and visits by mothers of toddlers at the integrated health post with a p-value of 0.016 and there was a correlation between motivation and visits by mothers of toddlers at the integrated health post with a p-value of 0.004. The researcher suggests that the Lingkar Timur Health Center increase the knowledge, understanding and motivation of mothers of toddlers about visits to the integrated health post by using appropriate promotional media such as leaflets, posters and others through counseling to each integrated health post.